Role of the National Land Agency in Settlement of Land Boundary Disputes in Jayapura City - Palenewen, James Yoseph (PT. Riset Press International, 2023)
The important role of the National Land Agency in resolving land boundary disputes in Jayapura City cannot be ignored. Many problems arise from land disputes due to the non-implementation of the Delimitation Contradictory Principle, namely the principle relating to the measurement and determination of land boundaries by the BPN. The aim is to find out the application of the Delimitation Contradictory Principle at the Jayapura City Land Office and also to find out the settlement of land disputes due to the non-applicability of the Delimitation Contradictory Principle at the Jayapura City Land Office. The method used in this research is normative and empirical law seen from the applicable laws and regulations and the reality that occurs in the field. The findings of this study indicate that the application of the Delimitation Contradictory Principle at the Jayapura City Land Office is actually according to procedure. However, there are internal problems with the old maps which have been lost and damaged, so there is often overlapping of plots of land. Apart from that, the absence of bordering parties in the field also often occurs, so that BPN must entrust the measuring drawing filling sheet. This causes the application of the Delimitation Contradictory Principle to not run properly, and land disputes cannot be resolved properly. To overcome this, BPN facilitates mediation for the disputing parties so that they do not proceed to more serious problems and even lawsuits in court. if it has not been resolved, a team is formed to deal with it and find a solution so that the problems experienced by the parties do not need to go to court and all this is carried out according to the procedures in the applicable laws and regulations.